Hold it All Together: a Case Study in Quality Control for Born-Digital Archiving - Weston, Paul Gabriele; Carbé, Emmanuela; Baldini, Primo (Qualitative and Quantitative Methods in Libraries, 2017)
PAD (Pavia Archivi Digitali) is a project developed at the University of Pavia aiming at long-term preservation of born-digital private and literary papers produced by Italian writers and journalists. Since 2009, when the first collection was entrusted to PAD, the archive has grown and it currently includes almost 80,000 files. Dealing with this material is inherently complex, as it implies the integration of fields such as literary studies, archival techniques, information technology, and legal and administrative matters. In particular, evolution in technology, use of different types and versions of software, ever changing storage techniques, from floppy disks to cloud services, are all factors posing severe challenges. To ensure a rigorous management of the workflow, which is critical to the success of the entire project, a specific piece of sofware - QUANDO (Quality control for Archiving and Networking Digital Objects) - was developed.